KESEJAHTERAAN PSIKOLOGIS PADA ISTRI YANG MENGALAMI KEKERASAN DALAM RUMAH TANGGA - HERDIYAN MAULANA; MEI LESTARI SEKAR DININGRUM (Journal of Research and Measurement in Psychology, 2015)
This research aims to know the psychological well-being reflections on intimate-partner-violence-suffering wives who end up in a divorce. Subjects used in this research are two persons. Characteristic samples in this research are women aged 20-30 years who are divorced and have offspring. Research type is in the form of Research Qualitative Case Study. Data intake is the interview and observation methods. This interview is not only conducted to the subjects, but also to the respective significant person who is assumed the nearest to the subjects. Based on the research, Subject I is recorded to have supporting factors to psychological well-beings which are social supports, reflected appraisals, behavioral self-perceptions and religiousness. On the other hand, Subject II is recorded to have supporting factors to psychological well-beings like social supports, social comparisons, reflected appraisals, behavioral self-perceptions, religiousness, marriage motivation, economic factors and divorce age. In general, Subject I has lower level of psychological well-beings than those of Subject II.